Analisis Akurasi Penentuan Harga Jual Barang Menggunakan Metode Mark Up Pricing Berbasis Sistem Informasi - Muhammad Krisza Aditya; R. Rhoedy Setiawan; Yudie Irawan (Pusat Riset dan Inovasi Nasional, 2026)
The An-Nizam Jepara grocery store currently faces several challenges in managing sales transaction data, determining selling prices, and managing inventory data due to the continued use of paper-based or conventional recording methods. This results in errors in recording inventory data and inconsistencies in pricing. This research aims to assist the An-Nizam grocery store in addressing these challenges by developing an inventory and sales system integrated with stock management and financial accuracy. The development method used is the Waterfall System Development Life Cycle (SDLC) model, which is highly dynamic and structured. To solve the pricing problem, the Mark-Up Pricing method is used within the system to automatically calculate the selling price based on the desired profit percentage. This system was developed using the Laravel framework and a MySQL database. The expected outcome of this research is the creation of an inventory and sales system that can minimize human error, streamline sales transaction processes, and provide stock reports based on specific periods or in real time. This system is expected to help the An-Nizam grocery store determine better selling prices and maintain good and efficient stock management.